EVALUATION AND MONITORING IN EDUCATION MANAGEMENT - Noneng Nurhayani; Al-Amin (Adisam Publisher, 2025)
Evaluation and monitoring in education management are critical components that support the improvement of the quality and effectiveness of educational institutions. Therefore, it is important to implement a comprehensive evaluation and monitoring system as a tool to analyse and optimise the teaching and learning process as well as the day-to-day operations of educational institutions. Through evaluation, the strengths and weaknesses of the education system can be identified, providing a basis for strategic decision-making and more efficient resource allocation. Continuous monitoring ensures that any quality improvement initiatives are not only implemented but also receive systematic feedback for further refinement. In addition, this process supports increased transparency and accountability of educational institutions, strengthens public trust and promotes a culture of continuous quality improvement. Thus, evaluation and monitoring become not only a measuring tool for institutional performance but also a catalyst for the development of education that is innovative and responsive to future challenges.